Genetic Characterization and Phylogenetic Analysis of Fasciola Species Isolated From Yaks on Qinghai-Tibet Plateau, China - Gao, Xing; Wang, Dongjing; Zhang, Zhao; Quan, Chuxian; Zhou, Shimeng; Li, Kewei; Li, Yan; Zhao, Suonan; Kong, Xiangying; Kulyar, Muhammad Fakhar-e-Alam; Zeng, Jiangyong; Li, Jiakui (Frontiers in Veterinary Science, 2022)
The present study determined the complete mitochondrial DNA (mt DNA) sequence of Fasciola intermediate (isolated from yaks) based on gene content and genome organization. According to our findings, the genome of Fasciola intermediate was 13960 bp in length, containing 2 ribosomal RNA (rRNA) genes, 12 protein-coding genes (PCGs), and 22 transfer RNA (tRNA) genes. The A+T content of genomes was 63.19%, with A (15.17 %), C (9.31 %), G (27.51 %), and T as the nucleotide composition (48.02 %). Meanwhile, the results showed negative AT-skew (-0.52) and positive GC-skew (0.494). The AT bias significantly affected both the codon usage pattern and amino acid composition of proteins. There were 2715 codons in all 12 protein-coding genes, excluding termination codons. Leu (16.72 %) was the most often used amino acid, followed by Val (12.74 %), Phe (10.90 %), Ser (10.09 %), and Gly (8.39 %). A phylogenetic tree was built using Maximum-Likelihood (ML) through MEGA 11.0 software. The entire mt DNA sequence of Fasciola intermediate gave more genetic markers for investigating Trematoda population genetics, systematics, and phylogeography. Hence, for the first time, our study confirmed that yaks on the Qinghai-Tibet plateau have Fasciola intermediate.